Evaluasi Tarif Angkutan Feeder Wirawiri Suroboyo FD01 Berdasarkan Aspek Biaya Operasional Kendaraan (BOK), Willingness To Pay (WTP), Dan Ability To Pay (ATP) - Hapsari, Maharanny Wahyu; Sholichin, Ibnu; Utomo, Nugroho (Jurnal Talenta Sipil, 2025)
The price or tariff spent by passengers is one of the main factors in determining the quality of Wirawiri Suroboyo feeder public transport. Also, tariffs can be an important consumer consideration when buying transportation services. Therefore, it is necessary to evaluate the current tariff to determine the optimal tariff for both consumers and service providers. Primary data collection methods are carried out by distributing questionnaires to passengers of Wirawiri Suroboyo feeder transportation Route FD01 Benowo Terminal - Tunjungan, and interview surveys of Vehicle Operating Costs at the Technical Implementation Unit of the Public Transportation Management Office and the Transport Division of the Surabaya City Transportation Agency. Secondary data collection methods were obtained from the Technical Implementation Unit of the Public Transportation Management Office of Surabaya City. The completion of this study uses calculations based on Vehicle Operating Costs, Willingness to Pay method, and Ability to Pay method. The results of this study found that the Wirawiri Suroboyo feeder transportation tariff Route FD01 based on Vehicle Operating Costs is IDR14,000/passenger, based on WTP calculation is IDR4,000/passenger, and based on ATP calculation is IDR7,100/passenger. Therefore, it can be said that the current tariff of IDR5,000 is good because it is below the willingness and ability of passengers to pay.